PENILAIAN HAKIM TERHADAP ALAT BUKTI MEREK TERKENAL “LEGEND”: Judge’s Assessment of Evidence Regarding the Famous “Legend” - Najwa Qonita Hasan; Ning Adiasih (Reformasi Hukum Trisakti, 2025)
The trademark "LEGEND" owned by Sandi Hakim, which was previously registered in Indonesia, was challenged for cancellation by Wahl Clipper Corporation (WCC) from the United States on the grounds that "LEGEND" was a well-known trademark owned by WCC, thereby granting WCC the right to register it under the Indonesian legal system. In this case, the court ruled in favor of Wahl Clipper Corporation based on the judge’s consideration that the trademark was indeed well-known.The issues raised in this research is: why the judge granted the claim and declared the plaintiff’s trademark as a well-known mark despite it not being registered in multiple countries. This research uses a normative juridical approach, with descriptive research aimed at describing and analyzing legal norms from legislation and court decisions. In its ruling, the judge relied on Ministry of Law and Human Rights Regulation No. 67/2016 rather than the Trademark and Geographical Indications Law No. 20/2016 in case number 532 K/Pdt.Sus-HKI/2024. It can be concluded that the judge did not apply the principle of Lex Superior Derogat Legi Inferiori, leading to legal uncertainty and disregarding the constitutive protection of legally registered trademarks in Indonesia.